The Effects of Learning Styles and Gender on Computational Thinking Skills in Biology Learning among Indonesian High School Students - Animah, Faza; Wijayanti, Erna; Tauhidah, Dian (Universitas Muhammadiyah Surakarta, 2025)
Computational Thinking (CT) needs to be integrated into education as essential preparation for facing the Society 5.0 era. These skills are fundamental and relevant not only in computer science but also across various disciplines, including biology. This study aims to examine the simultaneous and partial effects of learning styles and gender on students' CT skills. This is a quantitative, non-experimental study using dummy regression analysis. The research subjects consisted of 128 grade XII science students at SMAN 1 Semarang, with data collected through questionnaires and tests. The results showed that: (1) Learning styles and gender simultaneously had a significant effect on students' CT abilities, with a contribution of 14.1% and an F change significance value of 0.00. (2) Learning styles had no significant effect on CT (significance > 0.05). (3) Gender had a significant effect on CT (significance < 0.05). These findings provide valuable insights for the development of learning strategies that go beyond gender and learning preferences, by also considering other, more dominant factors influencing Computational Thinking skills. Therefore, teachers are expected to be more responsive to differences in learning pace and strategies across genders, and to design inclusive instruction to optimize the full potential of every student.